Disagreeing respectfully: Embracing complexity facilitates civil discourse - Lefkowitz, Ariel; Maniate, Jerry M; Kuper, Ayelet (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Polarization and incivility are on the rise, negatively affecting collegiality, workplace relationships, morale, and performance at work. The authors argue for the need for civil discourse in medicine and for embracing complexity as an essential component of that civil discourse, facilitating nuanced thinking, respectful dialogue, and greater understanding of other perspectives. This principle of embracing complexity is congruent with the attitude of physicians, who are trained to tolerate uncertainty and to hold and appreciate multiple perspectives in making diagnoses and choosing and proposing treatment plans. This understanding of civil discourse does not amount to moral relativism, whataboutism, or an embracing of both sides of an argument universally, nor does it serve as a cudgel to silence or to perpetuate hegemonic power. Instead, the principles of civil discourse clarify multiple aspects of the boundaries of professional conduct, outlining how physicians can engage in advocacy for patients and communities while maintaining collegial relationships and the perception that they will be safe providers for all patients. The rights of citizens in democracies, including to engage in peaceful protest and to say anything within the bounds of their country’s laws governing free speech, do not extend unabbreviated into the lives of professionals, who are limited by the privileges afforded to them and by the responsibilities they have to their patients and colleagues. By embracing complexity and nuance over simplism and slogans, physician colleagues who disagree with one another can communicate respectfully, advocate professionally, and be safe and effective care providers to all patients.